The scientific production of the research productivity scholars at UFAL: analysis of disciplinary and utilitarian trends (Seminário Internacional de Informação, Tecnologia e Inovação, 2025)
The Research Productivity Fellows affiliated with the Federal University of Alagoas (UFAL) represent the scientific production elite not only at the state level but also at the national level. Their contributions strengthen their respective fields of knowledge. This study aims to characterize the disciplinary and utilitarian productivity trends of UFAL Research Productivity Fellows over the last six decades. Methodologically, the research is descriptive with a primarily qualitative approach. The study examines the contributions of 100 UFAL Research Productivity Fellows. A total of 12,389 disciplinary and 309 utilitarian outputs were identified. The trends demonstrated through quantitative data provide an overview of the scientific output of UFAL fellows, grouped by major field.